2018
DOI: 10.1007/s00405-018-4944-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers in well-differentiated thyroid cancer

Abstract: The prevalence of these mutations in thyroid nodule is high and it is a continuously evolving field. Clinicians should stay informed as recommendation on the use of these markers is expected to evolve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 85 publications
1
28
0
4
Order By: Relevance
“…There has been a worldwide thyroid epidemic with 470,000 women and 90,000 men being diagnosed during the last two decades. Though the disease-specific mortality of thyroid cancer is low, unwarranted or inadequate surgery is associated with increased morbidity making proper management important ( D’Cruz et al, 2018 ). The promotion of Xn on I - uptake of FRTL-5 thyrocytes suggested that Xn might be an interesting candidate for increasing the sensitivity of radiotherapy on thyroid cancer ( Radovic et al, 2005 ).…”
Section: Head and Neck Cancersmentioning
confidence: 99%
“…There has been a worldwide thyroid epidemic with 470,000 women and 90,000 men being diagnosed during the last two decades. Though the disease-specific mortality of thyroid cancer is low, unwarranted or inadequate surgery is associated with increased morbidity making proper management important ( D’Cruz et al, 2018 ). The promotion of Xn on I - uptake of FRTL-5 thyrocytes suggested that Xn might be an interesting candidate for increasing the sensitivity of radiotherapy on thyroid cancer ( Radovic et al, 2005 ).…”
Section: Head and Neck Cancersmentioning
confidence: 99%
“…In addition, 10%‐15% of PTC patients are still prone to relapse and distant metastasis, leading to a poor prognosis . Many studies have identified that genetic mutations and environmental factors are important in thyroid carcinogenesis, but many of the molecular mechanisms underlying TC pathogenesis remain unknown . Therefore, understanding the potential molecular mechanism underlying the oncogenesis and progression of TC is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal DNA methylation, including a decrease in the overall methylation level of the genome, was accompanied by hypermethylation in some gene promoter regions. The hypermethylation of tumor suppressor gene promoter can reduce its expression, while the hypomethylation of tumor suppressor gene promoter can increase its expression, leading to tumorigenesis [5][6][7][8]. The following will describe the state of aberrant DNA methylation in different thyroid cancers.…”
Section: Introductionmentioning
confidence: 99%